Integrating Financial Management and Gamification: A Systematic Literature Review and Future Research Agenda - Prasetyo, Amrisandha Pranantya; Santoso, Harry Budi; Putra, Panca Oktavia Hadi (The Indonesian Journal of Computer Science, 2023)
The implementation of gamification in PFM apps has the potential to motivate users to engage in positive financial behaviors. However, several research gaps corroborate the need to investigate gamification in the financial domain further. To address these gaps, this systematic literature review comprehensively examines current research on financial behavior and gamification. This review utilizes the Theory, Context, Characteristics, and Methodology (TCCM) framework to provide a holistic understanding of financial behavior and gamification-related behavioral intention. A total of 53 articles published between 2018 and 2022 were analyzed to assess the present research landscape and provide directions for future studies. This review makes three key contributions: (1) synthesizes current research on financial behavior and gamification-related behavioral intention, (2) presents integrated conceptual models that elucidate financial behavior and gamification-related behavioral intention, and (3) identifies research gaps and suggests avenues for future investigation.